Plano de comunicação em jornalismo científico para a assessoria de imprensa / CODECOM da UEPB - Queiroz, Giuliana Batista Rodrigues de (2017)
This work is focused on the elaboration of a media product, which consists in an intervention project in the communication of the State University of Paraíba. Through it, we propose means and tools with the purpose to improve the informative process that takes the scientific researches developed in the Institution for the society, contributing to the improvement of the dissemination of the UEPB's scientific knowledge to the media and, consequently, for the community in general. The development of this Communication Plan emerges as a possibility to combine theory and practice to integrate the work of the Press Office the actions that make the most effective science journalism service. Investigative strategies are presented, such as bibliographic researches and the application of questionnaires to the professors/researchers of the Institution; as well as the participatory methodologies, based on visits to the eight UEPB campuses, where workshops were ministered which worked as methodological tools and as means of integration with an academic community; and on the construction of media and educational products, such as the information booklet "Be an Employee of the UEPB's Communication Coordination" and a specific site in scientific journalism, www.cientifica.uepb.edu.br. The Communication Plan is grounded in the concepts of Organizational Communication (KUNSCH, 2008, 1992; BUENO, 2014; SÓLIO, 2008), Press Office (DUARTE, 2001; MAFEI, 2015; KOPPLIN e FERRARETTO, 2001), Disclosure and Scientific Journalism (SOUSA, 2006; BUENO, 2010), besides the principles of Participant Observation, the Research-Action and Research Participant (BARBIER, 1985, 2002; PERUZZO, 2006; THIOLLENT, 2005; RICHARDSON, 2003). Although the present media project does not end in this proposal, considering that these were the first initiatives and the first products created with specific focus in the scientific journalism of the University, it is understood that they begin to be presented to the academic community and to generate greater interest and participation to improve quantitatively and qualitatively the dissemination of UEPB's scientific research, enriching the offer of services of Codecom and of the whole University.